To remove brackets, we multiply the term on the outside of the bracket with each term inside the bracket.

This process to remove brackets is also known as the distributive law.

Remove the brackets for the expression \(4(y - 5)\).

This expression means everything inside the brackets is multiplied by 4.

\[= (4 \times y) - (4 \times 5)\]

\[= 4y - 20\]

- Question
Multiply out the brackets in \(3(2a + 5)\)

\[= (3 \times 2a) + (3 \times 5)\]

\[= 6a + 15\]

- Question
Multiply out the brackets in \(5(3 - y)\)

\[= (5 \times 3) - (5 \times y)\]

\[= 15 - 5y\]

- Question
Multiply out the expression \(2(6 - 4y)\)

\[= (2 \times 6) - (2 \times 4y)\]

\[= 12 - 8y\]

- Question
Remove the brackets from \(4(3w - 2y)\)

\[= (4 \times 3w) - (4 \times 2y)\]

\[= 12w - 8y\]

- Question
Remove the brackets from \(2(2x + 3y - 7z)\)

\[= (2 \times 2x) + (2 \times 3y) - (2 \times 7z)\]

\[= 4x + 6y - 14z\]